Quality of Life in Women After Pelvic Exenteration for Gynecological Malignancies: A Multicentric Study. Issue 2 (February 2018) - Dessole, Margherita; Petrillo, Marco; Lucidi, Alessandro; Naldini, Angelica; Rossi, Martina; De Iaco, Pierandrea; Marnitz, Simone; Sehouli, Jalid; Scambia, Giovanni; Chiantera, Vito
Abstract : Objectives: This retrospective, multicentric study investigates quality-of-life issues and emotional distress in gynecological cancer survivors submitted to pelvic exenteration (PE). Methods: The Global Health Status scale of European Organization for Research and Treatment of Cancer (EORTC) Core Quality of Life Questionnaire (QLQ-C30; the EORTC QLQ-CX24 (CX24), and EORTC QLQ-OV28 questionnaires were administered at least 12 months from surgery only in women with no evidence of further recurrence after PE. Statistical analysis was performed by the analysis of variance (for repeated measures. Results: Ninety-six subjects affected by gynecological malignancies receiving PE were enrolled in the study. Anterior PE was performed in 47 patients (49%), posterior PE was performed in 29 cases (30.2%), and total PE performed in 20 women (20.8%). In 38 cases (39.6%), a definitive colostomy was performed. Urinary diversion with continent pouch was created in 11 patients. (11.5%), whereas in the remaining cases, a noncontinent pouch was reconstructed. Patients showed a significant discomfort in attitude to disease (71.5 ± 4.7), body image (48.9 ± 6.4), financial difficulties (56.2 ± 5.8), gastrointestinal symptoms (constipation, 47.8 ± 5.1; diarrhea, 62.4 ± 6.6; appetite loss, 43.6 ± 6.7), insomnia (64.5 ± 6.6), Global Health Status (64.6 ± 3.8), physical functioning (65.8 ± 4.6), role functioning (58.8 ± 5.8), and emotional functioning (67.4 ± 4.2). A higher number of ostomies (hazard rate [HR], 7.613; P = 0.012), the creation of a noncontinent bladder (HR, 8.230; P = 0.009), and of definitive colostomy (HR, 8.516; P = 0.008) emerged as independent predictors of poorer Global Health Status scores. Older age (HR, 11.235; P = 0.003), vaginal/vulvar cancer (HR, 7.369; P = 0.013), total/posterior PE (HR, 7.393; P = 0.013), higher number of ostomies (HR, 7.613; P = 0.012), the creation of a noncontinent bladder (HR, 8.230; P = 0.009), and of definitive colostomy (HR, 8.516; P = 0.008) emerged as independent predictors of lower body image levels. Conclusions: Long-term psycho-oncological support is strongly recommended. The reduction of ostomies seems the most effective way to improve patients' quality of life. Abstract : Supplemental digital content is available in the text.